Socialization of Filling in Completeness of Medical Record Resume and Accuracy of Diagnostic Code of Surgical Treatment Unit for BPJS Patients on Submission of Inpatient Service Claims - Yulia Fitriani; Deni Maisa Putra; Dian Novita; Anisah Amartia (Indonesian Journal of Health Information Management Services, 2022)
ABSTRACT. The completeness of the medical resume and the accuracy of the diagnosis code will affect the information generated due to the inaccuracy of the data presented so that it has an impact on the quality of information and the accuracy of the code in accordance with ICD-10. In RSI Ibnu Sina Padang, incomplete and inaccurate medical resumes are still found. This study aims to determine the review of the completeness of the medical resume and the accuracy of the diagnostic code of the surgical care unit for BPJS patients on filing BPJS claims for inpatient surgical care units. This type of research is descriptive, to see a description of the completeness of the medical resume and the accuracy of the diagnosis code of the surgical care unit for BPJS patients for submitting claims for inpatient services. The study was carried out in the case mix surgical treatment unit at Ibnu Sina Hospital. Data collection method using univariate analysis. The results showed that the completeness of the incomplete medical resume was (30.9%), the accuracy of the inaccurate diagnosis code was 14.8%, and there were no claims pending for BPJS claims. Based on the results of the study, it can be concluded that the incompleteness of the medical resume and inaccuracies are still not maximized, the researchers suggest paying attention to the medical record officer/coder starting from compliance with applicable regulations and policies, so that the completeness of the medical resume and the accuracy of the diagnosis code can be achieved as expected.